Phase II Study of the MEK1/MEK2 Inhibitor Trametinib in Patients With Metastatic BRAF-Mutant Cutaneous Melanoma Previously Treated With or Without a BRAF Inhibitor - Kim, Kevin B. (J Clin Oncol, 2013)
PURPOSE: BRAF mutations promote melanoma cell proliferation and survival primarily through activation of MEK. The purpose of this study was to determine the response rate (RR) for the selective, allosteric MEK1/MEK2 inhibitor trametinib (GSK1120212), in patients with metastatic BRAF-mutant melanoma. PATIENTS AND METHODS: This was an open-label, two-stage, phase II study with two cohorts. Patients with metastatic BRAF-mutant melanoma previously treated with a BRAF inhibitor (cohort A) or treated with chemotherapy and/or immunotherapy (BRAF-inhibitor naive; cohort B) were enrolled. Patients received 2 mg of trametinib orally once daily. RESULTS: In cohort A (n = 40), there were no confirmed objective responses and 11 patients (28%) with stable disease (SD); the median progression-free survival (PFS) was 1.8 months. In cohort B (n = 57), there was one (2%) complete response, 13 (23%) partial responses (PRs), and 29 patients (51%) with SD (confirmed RR, 25%); the median PFS was 4.0 months. One patient each with BRAF K601E and BRAF V600R had prolonged PR. The most frequent treatment-related adverse events for all patients were skin-related toxicity, nausea, peripheral edema, diarrhea, pruritis, and fatigue. No cutaneous squamous cell carcinoma was observed. CONCLUSION: Trametinib was well tolerated. Significant clinical activity was observed in BRAF-inhibitor–naive patients previously treated with chemotherapy and/or immunotherapy. Minimal clinical activity was observed as sequential therapy in patients previously treated with a BRAF inhibitor. Together, these data suggest that BRAF-inhibitor resistance mechanisms likely confer resistance to MEK-inhibitor monotherapy. These data support further evaluation of trametinib in BRAF-inhibitor–naive BRAF-mutant melanoma, including rarer forms of BRAF-mutant melanoma.